Effect of Acarbose on Long-Term Prognosis in Acute Coronary Syndromes Patients with Newly Diagnosed Impaired Glucose Tolerance - Peng Yun; Ai-ming Du; Xue-jun Chen; Jing-cheng Liu; Hu Xiao (Journal of Diabetes Research)
Objective. To investigate the effect of acarbose therapy on the long-term prognosis of patients with acute coronary syndromes (ACS) complicating newly diagnosed impaired glucose tolerance (IGT). Methodology. 135 patients hospitalized for ACS who had been newly diagnosed with IGT were randomly assigned to acarbose group (150 mg/day, n=67) or control group (no acarbose, n=68). All cases in each group were given the same elementary treatment. Mean follow-up was 2.3 years. The incidence of major adverse cardiovascular event (MACE) and carotid intima-middle thickness (CIMT) were statistically analyzed. Results. During the mean follow-up of 2.3 years, the risk of recurrent MACE in acarbose group was decreased significantly compared with that in control group (26.67% versus 46.88%, P<0.05); at the same time, thickening of the CIMT was significantly slower than the control group ((1.28 ± 0.42) mm versus (1.51 ± 0.64) mm, P<0.05). Conclusions. Acarbose can effectively reduce the risk of MACE in ACS patients with newly diagnosed IGT, simultaneously retarding the progression of carotid intima-media thickness.